Pengaruh Strategi React Terhadap Penalaran Induktif Matematis Dan Motivasi Belajar Matematika Siswa SMP - Tri Astuti Arigiyati; Agustina Sri Purnami; Rizka Arinil Haq (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2017)
The purpose of this research are to know (1) the influence using REACT learning strategy about increase student’s mathematical inductive reasoning skills, and (2) the influence using REACT learning strategy about increase student’s studying motivation. Population of this research was the students grade VIII of SMP. The sample was 34 students as the experimental class that given treatment REACT learning and 31student as the control class with expository learning. Data collection in this study by using test and questionnaire techniques. Data were analyzed by using t test. The result of the research showed that 1) the value of sig 0,03 <0,05 meaning that there is influence of applying of REACT learning to improvement of mathematical inductive reasoning ability of student of class VIII SMP, (2) sig value 0,041 <0,05 meaning that there is influence of application of REACT learning to increase motivation learn math class VIII SMP.